Pengaruh Pemberdayaan Wanita Terhadap Pertumbuhan Ekonomi Melalui Usaha Makanan Halal (UMKM) - Atiah, Isti Nuzulul; Najib, Mohamad Ainun; Najmudin, Najmudin (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2024)
This research aims to analyze the relationship between women's empowerment and economic growth through halal food MSMEs. This research use the path analysis method (Structural Equation Modeling - SEM) to examine the relationship between women's empowerment variables (such as education, access to resources, and role in decision making) and economic growth through a mediator variable, namely the performance of halal food MSMEs. The results of this research show that based on the SEM test results, women's empowerment (through access to education, capital and policy support) significantly improves the performance of halal food MSMEs. Likewise, better performance of MSMEs contributes significantly to economic growth (increasing GDP, employment, and increasing living standards). This means that women's empowerment also has a direct influence on economic growth, although it is smaller than the influence through the performance of MSMEs